Hsp60 Post-translational Modifications: Functional and Pathological Consequences - Caruso Bavisotto, Celeste; Alberti, Giusi; Vitale, Alessandra Maria; Paladino, Letizia; Campanella, Claudia; Rappa, Francesca; Gorska, Magdalena; Conway de Macario, Everly; Cappello, Francesco; Macario, Alberto J. L.; Marino Gammazza, Antonella (Frontiers in Molecular Biosciences, 2020)
Hsp60 is a chaperone belonging to the Chaperonins of Group I and typically functions inside mitochondria in which, together with the co-chaperonin Hsp10, maintains protein homeostasis. In addition to this canonical role, Hsp60 plays many others beyond the mitochondria, for instance in the cytosol, plasma-cell membrane, extracellular space, and body fluids. These non-canonical functions include participation in inflammation, autoimmunity, carcinogenesis, cell replication, and other cellular events in health and disease. Thus, Hsp60 is a multifaceted molecule with a wide range of cellular and tissue locations and functions, which is noteworthy because there is only one hsp60 gene. The question is by what mechanism this protein can become multifaceted. Likely, one factor contributing to this diversity is post-translational modification (PTM). The amino acid sequence of Hsp60 contains many potential phosphorylation sites, and other PTMs are possible such as O-GlcNAcylation, nitration, acetylation, S-nitrosylation, citrullination, oxidation, and ubiquitination. The effect of some of these PTMs on Hsp60 functions have been examined, for instance phosphorylation has been implicated in sperm capacitation, docking of H2B and microtubule-associated proteins, mitochondrial dysfunction, tumor invasiveness, and delay or facilitation of apoptosis. Nitration was found to affect the stability of the mitochondrial permeability transition pore, to inhibit folding ability, and to perturb insulin secretion. Hyperacetylation was associated with mitochondrial failure; S-nitrosylation has an impact on mitochondrial stability and endothelial integrity; citrullination can be pro-apoptotic; oxidation has a role in the response to cellular injury and in cell migration; and ubiquitination regulates interaction with the ubiquitin-proteasome system. Future research ought to determine which PTM causes which variations in the Hsp60 molecular properties and functions, and which of them are pathogenic, causing chaperonopathies. This is an important topic considering the number of acquired Hsp60 chaperonopathies already catalogued, many of which are serious diseases without efficacious treatment.